2020
DOI: 10.1186/s40545-020-00269-5
|View full text |Cite
|
Sign up to set email alerts
|

Generic versus brand-name over-the-counter analgesics: knowledge and attitudes among Swedish pharmacy customers

Abstract: Background Due to a liberalisation reform in 2009, the availability of over-the-counter (OTC) analgesics has increased significantly in the Swedish market over the past decade. With the increasing number of generic products available on the market and the possibility of buying OTC drugs from non-pharmacy outlets, a key to safe drug use is that consumers possess the necessary knowledge to differentiate between the different brands and choose the appropriate drug for their ailments. The aim of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…When confronted with the names of four active ingredients and a short list of brand names, only one-third were able to match at least three active substances to the correct brand. 24 This is in line with the results of West et al, which showed that only 30% of NSAID-users were able to recall the generic or brand name of the medicine. 11 The participants in this cohort were middle-aged women (38 or 50 years of age) whose average score on general health (SF36 domain) was higher than that reported in a previous population-based study from Gothenburg, 25,26 indicating a rather healthy study population.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…When confronted with the names of four active ingredients and a short list of brand names, only one-third were able to match at least three active substances to the correct brand. 24 This is in line with the results of West et al, which showed that only 30% of NSAID-users were able to recall the generic or brand name of the medicine. 11 The participants in this cohort were middle-aged women (38 or 50 years of age) whose average score on general health (SF36 domain) was higher than that reported in a previous population-based study from Gothenburg, 25,26 indicating a rather healthy study population.…”
Section: Discussionsupporting
confidence: 88%
“…When confronted with the names of four active ingredients and a short list of brand names, only one-third were able to match at least three active substances to the correct brand. 24 This is in line with the results of West et al, which showed that only 30% of NSAID-users were able to recall the generic or brand name of the medicine. 11 …”
Section: Discussionsupporting
confidence: 88%
“…ln the present study, respondents did not prefer local paracetamol to branded tablets due to its lower cost (99%). But in other comparative study, 69.4% [ 23 ] of the participants choose the cheaper generic over brand OTC medicines. In Saudi Arabia, 51.8% of the participants did not prefer using GMs because of their low price [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, in another study, the majority of respondents associated low cost or no cost with lower quality of medicine [ 26 ]. The reasons why consumers did not opt for the local one maybe because they perceive cheaper medicines are inferior in quality [ 13 , 23 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Females visit pharmacies more frequently and may receive more information about drugs. A previous study in Sweden showed that females paid more attention to drug efficacy (Håkonsen et al, 2020). Compared to people without chronic diseases, people with chronic diseases pay more attention to drug efficacy due to the need for frequent medication, and they need cost-effective and effective medicines to treat diseases and relieve symptoms.…”
Section: Analysis Of Influencing Factors Of Residents Taking Drug Saf...mentioning
confidence: 99%